Comparison of CSF biomarkers in Down syndrome and autosomal dominant Alzheimer's disease: a cross-sectional study. Issue 8 (August 2021) - Fagan, Anne M; Henson, Rachel L; Li, Yan; Boerwinkle, Anna H; Xiong, Chengjie; Bateman, Randall J; Goate, Alison; Ances, Beau M; Doran, Eric; Christian, Bradley T; Lai, Florence; Rosas, H Diana; et al.
Summary: Background: Due to trisomy of chromosome 21 and the resultant extra copy of the amyloid precursor protein gene, nearly all adults with Down syndrome develop Alzheimer's disease pathology by the age of 40 years and are at high risk for dementia given their increased life expectancy compared with adults with Down syndrome in the past. We aimed to compare CSF biomarker patterns in Down syndrome with those of carriers of autosomal dominant Alzheimer's disease mutations to enhance our understanding of disease mechanisms in these two genetic groups at high risk for Alzheimer's disease. Methods: We did a cross-sectional study using data from adults enrolled in the Alzheimer's Biomarker Consortium-Down Syndrome (ABC-DS) study, a multisite longitudinal study of Alzheimer's disease in Down syndrome, as well as a cohort of carriers of autosomal dominant Alzheimer's disease mutations and non-carrier sibling controls enrolled in the Dominantly Inherited Alzheimer Network (DIAN) study. For ABC-DS, participants with baseline CSF, available clinical diagnosis, and apolipoprotein E genotype as of Jan 31, 2019, were included in the analysis. DIAN participants with baseline CSF, available clinical diagnosis, and apolipoprotein E genotype as of June 30, 2018, were evaluated as comparator groups. CSF samples obtained from adults with Down syndrome, similarly aged carriers of autosomal dominant Alzheimer's disease mutations, and non-carrier siblings (aged 30–61 years) were analysed for markers of amyloid β (Aβ1–40, Aβ1–42 ); tau phosphorylated at threonine 181-related processes; neuronal, axonal, or synaptic injury (total tau, visinin-like protein 1, neurofilament light chain [NfL], synaptosomal-associated protein 25); and astrogliosis and neuroinflammation (chitinase-3-like protein 1 [YKL-40]) via immunoassay. Biomarker concentrations were compared as a function of dementia status (asymptomatic or symptomatic), and linear regression was used to evaluate and compare the relationship between biomarker concentrations and age among groups. Findings: We assessed CSF samples from 341 individuals (178 [52%] women, 163 [48%] men, aged 30–61 years). Participants were adults with Down syndrome (n=41), similarly aged carriers of autosomal dominant Alzheimer's disease mutations (n=192), and non-carrier siblings (n=108). Individuals with Down syndrome had patterns of Alzheimer's disease-related CSF biomarkers remarkably similar to carriers of autosomal dominant Alzheimer's disease mutations, including reductions (all p<0·0080) in Aβ1–42 to Aβ1–40 ratio and increases in markers of phosphorylated tau-related processes; neuronal, axonal, and synaptic injury (p<0·080); and astrogliosis and neuroinflammation, with greater degrees of abnormality in individuals with dementia. Differences included overall higher concentrations of Aβ and YKL-40 (both p<0·0008) in Down syndrome and potential elevations in CSF tau (p<0·010) and NfL (p<0·0001) in the asymptomatic stage (ie, no dementia symptoms). Funding: National Institute on Aging, Eunice Kennedy Shriver National Institute of Child Health and Human Development, German Center for Neurodegenerative Diseases, and Japan Agency for Medical Research and Development.